An integrin-ILK-microtubule network orients cell polarity and lumen formation in glandular epithelium - Akhtar, Nasreen (2013)
The extracellular matrix has a crucial role in determining the spatial orientation of epithelial polarity and the formation of lumens in glandular tissues, however the underlying mechanisms remain elusive. By using Cre-Lox deletion we show that β1-integrins are required for normal mammary gland morphogenesis and lumen formation, both in vivo and in a 3D primary culture model where epithelial cells directly contact basement membrane. Downstream of basement membrane-β1-integrins, Rac1 is not involved, however ILK is needed to polarize microtubule plus ends at the basolateral membrane and disrupting each of these components prevents lumen formation. The integrin-microtubule axis is necessary for the endocytic removal of apical proteins from the basement membrane-cell interface and for internal Golgi positioning. We propose that this integrin-signalling network controls the delivery of apical components to the correct surface and thereby governs the orientation of polarity and development of lumens.